A novel variant in RyR2 causes familiar catecholaminergic polymorphic ventricular tachycardia. (January 2017) - Bosch, Cristina; Campuzano, Oscar; Sarquella-Brugada, Georgia; Cesar, Sergi; Perez-Serra, Alexandra; Coll, Monica; Mademont, Irene; Mates, Jesus; del Olmo, Bernat; Iglesias, Anna; Brugada, Josep; Petersen, Volker; et al.
Highlights: Catecholaminergic polymorphic ventricular tachycardia is a cause of sudden death. Molecular autopsy should be performed in sudden death cases showing normal autopsy. Next Generation Sequencing technology allows a comprehensive genetic analysis. Familial assessment is crucial to identify relatives at risk of sudden death. Abstract: Catecholaminergic polymorphic ventricular tachycardia is a rare familial arrhythmogenic disease. It usually occurs in juvenile patients with a structurally normal heart and causes exercise–emotion triggered syncope and sudden cardiac death. The main gene associated with catecholaminergic polymorphic ventricular tachycardia is RyR2, encoding the cardiac ryanodine receptor protein which is involved in calcium homeostasis. After the identification of a 16 year-old man presenting with exercise-induced sudden cardiac death, clinically diagnosed as catecholaminergic polymorphic ventricular tachycardia, we collected the family information and performed a comprehensive genetic analysis using Next Generation Sequencing technology. The initial electrocardiogram in the emergency department revealed ventricular fibrillation. On electrocardiogram monitoring, sinus tachycardia degenerated into bidirectional ventricular and into ventricular fibrillation. Catecholaminergic polymorphic ventricular tachycardia was clinically diagnosed in 5 of the 14 family members evaluated. There were no additional reports of seizures, pregnancy loss, neonatal death, or sudden cardiac death in family members. Genetic analysis of the index case identified only one rare novel variant p.Ile11Ser (c.32T>G) in the RyR2 gene. Subsequent familial analysis identified segregation of the genetic variant with the disease. All current evidence supports that novel p.Ile11Ser variant in the RyR2 gene is a potential disease-causing variant in catecholaminergic polymorphic ventricular tachycardia. To our knowledge, there has been no previous case report of catecholaminergic polymorphic ventricular tachycardia associated to this missense variant.